The deubiquitinylation and localization of PTEN are regulated by a HAUSP–PML network - Song, Min Sup (2008)
Nuclear exclusion of the PTEN tumour suppressor has been associated with cancer progression(1-6). However, the mechanisms leading to this aberrant PTEN localization in human cancers are currently unknown. We have previously reported that ubiquitinylation of PTEN at specific lysine residues regulates its nuclear-cytoplasmic partitioning(7). Here we show that functional PML-nuclear bodies co-ordinate PTEN localization by opposing the action of a novel PTEN-deubiquitinylating enzyme, HAUSP, and that the integrity of this molecular framework is required for PTEN to be able to enter the nucleus. We find that PTEN is aberrantly localized in acute promyelocytic leukaemia (APL), where PML function is disrupted by the PML-RARα fusion oncoprotein. Remarkably, treatment with drugs that trigger PML-RARα degradation such as all-trans retinoic acid or arsenic trioxide, restore nuclear PTEN. We demonstrate that PML opposes the activity of HAUSP towards PTEN, through a mechanism involving the adaptor protein DAXX. In support of this paradigm, we show that HAUSP is overexpressed in human prostate cancer and is associated with PTEN nuclear exclusion. Thus our results delineate a novel PML-DAXX-HAUSP molecular network controlling PTEN deubiquitinylation and trafficking, which is perturbed by oncogenic cues in human cancer, in turn defining a new deubiquitinylation-dependent model for PTEN subcellular compartmentalization.